Design Of Work Method In Order To Decreaseillness Rate Caused By Muscle And Nerve Dueto Unproper Work Method Using Ocra Index Ininstallation Department Pos Install Woodenlh And Routing Wiring In Pt. Xyz - Muhammad Nusem Hudiantoko; Rino Andias Anugraha; Yusuf Nugroho Doyo Yekti (eProceedings of Engineering, 2015)
Abstract Health is an important form of human capital. It can enhance worker’s productivity by increasing their physical capacities, such as strength and endurance, as well as their mental capacities, such as cognitive functioning and reasoning ability. Such in Vehicle logistics division, there is still 16% of total disease in PT XYZ are caused by nerve and muscle. By divide it into departement category, the most common disease is in Installation Operation which contributed 60%, it means that from the 16% disease caused by nerve and muscle 60% of infected operator are work in Installation Operation. In Installation Department operation there are five lines that have responsibility to install the available or given car. From the five lines, the most common is in line 2 which contribute 25%. Then identify each job in line 2 is the next step, and the most common is in Pos 2D which responsibility to install the wooden LH and routing. Then, the exisitng condition is assess by OCRA Index which evaluate four main collective risk factors based on their respective duration, which are repetitiveness, force, awkward posture and movements, and lack of proper recovery periods. Then, from the given result of assessment will be used as parameter to give an improvement which in term of an improvement work method. By improving the work system, the gap that has been categorized in OCRA Index has been fixed. In other words the OCRA Index for improvement condition is lower than the existing one. Means that the improvement process are sucessfully decreased the risk of illness from 2,449 to 1,054 by the OCRA Index assessment process. Key words: OCRA Index, Wooden LH, Nerve and Muscle, Routing, Repetitiveness, Awkward posture